Active Infrared Observation for Ice Detection in Anti/De-Icing Systems for Marine Applications in Arctic Region - Rashid, Taimur; Khawaja, Hassan Abbas (2016)
Poster presented at The International Conference of Multiphysics. Arranged by The International Society of Multiphysics, in Zurich, 08.12.16 - 09.12.16. The number of shipping operations is on the rise in the Arctic region. As a result of these increased activities, significant challenges are being encountered with respect to safety and reliability. One of the challenges is an accretion of ice. The icing on ships and offshore structures is caused by atmospheric sources and sea spray. The sea spray is the main source of icing and is generated by the wave collisions, the breaking of waves due to strong winds and bursting bubbles that float upon the waves. Heavy ice accretion poses a threat to the stability of ships and offshore structures by shifting their center of gravity. The study proposes an active infrared (IR) observation method for the detection of ice. This method is essential for automating the anti/de-icing systems, in particular for marine applications. There are a number of challenges to overcome before successfully deploying such a system. For example, adequate protection of the equipment and the electronics devices from the elements, ensuring proper functioning of electronic devices below zero temperatures, synchronizing of the IR image acquisition and processing / analysis and turning on/off timings of heating elements. The study focuses on identifying these technical issues and finding their appropriate remedies.